Hello sir .How can we factorise by spliting the middle terms?

Asked by  | 21st Jul, 2008, 04:56: PM

Expert Answer:

  • Solve x2 + 5x + 6 = 0. 
  • This is "quadratic equals zero", but, unlike the previous example, this isn't yet factored. The quadratic must first be factored, because it is only when you MULTIPLY and get zero that you can say anything about it. You can't conclude anything about the individual terms of the unfactored quadratic (like the 5x or the 6), because you can add lots of stuff that totals zero.

    So the first thing I have to do is factor:

    x2 + 5x + 6 =x2 + 3x+2x  + 6 = (x + 2)(x + 3)

    Set this equal to zero:

    (x + 2)(x + 3) = 0

    Solve each factor: Co

    x + 2 = 0  or  x + 3 = 0
    x = –2  or  x = – 3pyright © Elizabeth Stapel 2006-2008 All Rights Reserved

    The solution of x2 + 5x + 6 = 0 is x = –3, –2

Answered by  | 21st Jul, 2008, 06:54: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.